DIFFERENT TYPES OF NANOCARRIERS FOR TARGETED TREATMENT OF HIV/AIDS - OJAH, ANURUPA; BIPULNATH; DAS, TRISHNA (International Journal of Current Pharmaceutical Research, 2019)
AIDS is a major challenge in the 21st century. AIDS, stands for Acquired Immune Deficiency Syndrome, is a serious health problem and a fast-spreading incurable disease. It is a disorder of the cell-mediated immune system of the body. It is localized in certain inaccessible compartment of the body such as the CNS, lymphatic system and in the macrophages, where it cannot be reached by the majority of the therapeutic agent in adequate concentration or in which the therapeutic agents cannot for the necessary duration. HIV/AIDS infection are reducing incidence with the advent of Highly Active Antiretroviral Therapy (HAART). There remain a number of challenges including drug resistance, anatomical barriers to antiretroviral therapy. To overcome these different nanocarriers with the stimuli-responsive release are proposed for antiretroviral agents. Nanocarrier and those optimized for cancer chemotherapy. These include the development nanoparticles capable of passive and active targeting as well as those that are responsive to various internal and externl triggers. Nanocarriers can also provide many of the advantages of lipid system. Liposome, solid lipid nanoparticle, nanoemulsion, dendrimers, polymeric nanoparticle are the example of drug delivery systems that are under investigation for the treatment of HIV/AIDS. This review aims to summarize the ability of nanocarrier technology to provide a rational approach for anti-HIV therapy.